A clinical decision support system for managing flexor tendon injuries. (23rd January 2009) - Junankar, Prashant; Mital, Dinesh; Srinivasan, S.; Haque, Syed
A rule based clinical decision support system has been developed using the Exsys software for the flexor tendon injuries in zone II encompassing the continuum from injury to complete rehabilitation of the tendon. The system architecture uses the rules based logic blocks to create a decision support system, which takes the user through series of questions, and based on the answers input, the system will make the decisions. Hand therapists and hand surgeons have tested it. Two out of three hand therapists and two out of three hand surgeons concurred that the proposed systems is appropriate and will help in making good decisions and can be used by non-experts in familiar with basic knowledge of healthcare. The current accuracy of the system is good. We are in the process of inputting more knowledge in the system and targeting that 100% of hand therapists and hand surgeons will be satisfied with the performance of the system. Further refinement in the form of creating an internet based interactive system will be the natural next step for this project.